Simultaneous HPTLC Estimation of Ambroxol HCl and Cetirizine HCl in Their Combined Dose Tablet - B. BAGADE, SHASHIKANT; M. GOWEKAR, NARENDRA; V. KASTURE, AVINASH (Asian Journal of Chemistry, 2010)
A simple, rapid, reproducible and economical high performance thin layer chromatographic method for simultaneous estimation of ambroxol HCl and cetirizine HCl in tablet form has been developed. It was performed on silica gel 60 GF254 thin layer chromatographic plates using mobile phase comprising of methanol: ethyl acetate: toluene: ammonia (4:1:5:0.5:6: 1 drop) v/v and the detection was carried out at 231 nm showing Rf value 0.78 for ambroxol HCl and 0.40 for cetirizine HCl. The calibration curve response was observed between 4-10 μg for ambroxol HCl and 0.4-0.8 μg for cetirizine HCl by height and by area. The per cent drug estimated for ambroxol HCl and cetirizine HCl from marketed formulation was found to be 99.86 ± 1.72, 100.18 ± 2.0 by height and 100.81 ± 1.54, 99.13 ± 1.76 by area, respectively. The per cent recovery by height and by area was found to be 102.66 ± 1.53 and 100.04 ± 1.79 for ambroxol HCl and 99.31 ± 1.25 and 98.06 ± 1.45 for cetirizine HCl. The method was validated with the determination of accuracy, precision, specificity, linearity detector response and ruggedness.